2020
DOI: 10.3991/ijoe.v16i01.12263
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review Paper on Online Medical Mobile Applications in Malaysia

Abstract: <p class="0abstract"><strong>Abstract—</strong>The introduction of mobile devices to the worldwide market has marvelous possible to disturb the way Health care is providing. In this paper, we will overview the work done in the five years from 2014 to 2018 in the field of mHealth in Research perspective. For that purpose, we choose the Scopus database to review the past research published on mHealth in Malaysia. For that purpose, the quantitative review has been observed in bibliometric analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…The next step is to assess the level of effect size (f 2 ). Cohen [28] recommended that the f 2 values of 0.35, 0.15, and 0.02 were regarded as large, medium, and small effect sizes, respectively [29], [30], [31]. Table 7 shows the effect level of study size.…”
Section: Results and Findingsmentioning
confidence: 99%
“…The next step is to assess the level of effect size (f 2 ). Cohen [28] recommended that the f 2 values of 0.35, 0.15, and 0.02 were regarded as large, medium, and small effect sizes, respectively [29], [30], [31]. Table 7 shows the effect level of study size.…”
Section: Results and Findingsmentioning
confidence: 99%
“…Secondly, these services could be improved by using both direct clinical experience and formal hands on training [8]. Thirdly, it is recommended to follow the published and proven protocols and guidelines in assessing and treating patients [40], [38,39]. Lastly, it is found that the relations between the clients and clinic operators in addition to the inter-professional teamwork are key contributors of operationalizing the Tele-Health services [41].…”
Section: Discussionmentioning
confidence: 99%
“…Online education is the best method for both students and educators, especially during the different, long MCO phases [20]. Universities and other public and private higher education institutions had to consider the best alternatives to ensure that education activities could continue with less contact and as high quality as possible, and online learning was the only appropriate way [21]. However, several important factors while implementing online learning technology needed to be considered by the management of these institutions, such as speed of internet connectivity, coverage and time constraints faced by both educators and students [2].…”
Section: 3mentioning
confidence: 99%